A noção de organismo no fieri teórico de Carl Rogers: uma investigação epistemológica - Castelo Branco, Paulo Coelho (2010)
This master thesis proposes an epistemological inquiry within the concept of Organism as developed along the theoretical fieri of Carl Rogers. This fieri is hereby taken as representative of what to be made or to become in a science not arrested by its own previous conceptions. As to advance this research: it has been identified the phases among the theoretical fieri of Carl Rogers; the understanding of Rogers concerning the Organism as presented in each of his intellectual phases; considered the main theorists and academic influences Rogers recognized upon his own work; made explicit the broader epistemological frameworks which informed Rogers´ understanding of Organism. This thesis has been inspired by the historical-method developed by Jean Piaget as an epistemological approach for scientific research which focus on recognizing the ideas that have supported the development of a concept or a theory. This methodology was based in a deductive formulation as for what may have grounded the notion of Organism as formulated in the original texts as well as from those who were theoretically influential on Rogers´ system. Coming from a selection of those pieces of work explicitly referring to the concept of Organism, we may infer Rogers was profoundly part of this cultural moment. Not only restricted to assimilating and elaborating these diffused influences at his experience, his Organismic conceptualization turned possible the integration of different dimensions as such Personality (I/Me), Society (interrelations) and Nature (Cosmos). At each stage of his thought, Rogers indicated the following influences on the construction of that conception: (1) in non-directive couseiling – the functionalism-pragmatism north american and new psychoanalysis of Rank, Horney and Sullivan; (2) in client-centered therapy – repeat the previous influences and increases scientism and its north american applied Psychology, Gestalt Psychology and Kurt Lewin, educacional, social and politic philosophies, and theorists of personality; (3) in transition from client-centered therapy and person-centered approach, the impact of the experiencing concept of Gendlin, experience with groups, the performance in education, reflections of alternative perspectives and behavioral sciences and studies on organism and self-actualization Goldstein, Maslow, Angyal and allusions to Whyte; (4) in person-centered approach, it adds to studies of organism and self-actualization, the research of Szent-Gyoergy and the emergency of Capra, Prigogine and Maruyama systemic paradigm and holistic. This present thesis led us to reveal a new intelligibility traced with Rogers´ notion of Organism where emergency a cosmological approach for the person which does not restrain itself to the Personality. We understood Rogers was tracking his person-centered academic ground largely dependent on the new findings of the emergent contemporary science.